Analysis of Beginning Reading Skills of 2nd Grade Students at Integrated Islamic Elementary School Tahfidzul Quran An-Nahl Mataram - Thufail Mujaddid Al-Qoyyim; Siti Maulidiya Nabila; Muhaini Muhaini; Siti Hajariah; Affan Affan; Aida Atika Suri; Buntana Buntana (Balai Publikasi Indonesia, 2024)
Reading proficiency is a foundational skill in elementary education, significantly influencing students' academic success and personal development. This study investigates the initial reading abilities of 2nd-grade students at Integrated Islamic Elementary School Tahfidzul Quran An-Nahl, an institution that combines general and religious education. The research identifies key areas for improvement and evaluates the effectiveness of current teaching methods. Using a descriptive quantitative approach, the study assesses three main indicators: pronunciation accuracy, reading fluency, and voice clarity. Data were collected through reading tests and teacher questionnaires. Results reveal significant challenges, with most students rated as